Outcomes of haploidentical vs mismatched unrelated donor HCT with posttransplant cyclophosphamide prophylaxis - Yosra M. Aljawai; Jeremy Ramdial; Gabriela Rondon; Portia Smallbone; Partow Kebriaei; Uday Popat; Betul Oran; Katayoun Rezvani; Richard E. Champlin; Elizabeth J. Shpall; Rohtesh S. Mehta (Blood Advances)
Abstract: Limited data exist comparing haploidentical and mismatched unrelated donor (MMUD) hematopoietic cell transplantation (HCT) with posttransplantation cyclophosphamide for graft-versus-host disease prophylaxis, especially considering donor age. Herein, we report the outcomes of 660 haploidentical and 195 MMUD HCT recipients treated at MD Anderson Cancer Center. Beyond standard Cox proportional hazards modeling, we used inverse probability of treatment weighting (IPTW) and matched-pair analysis, and performed additional analysis by incorporating an external MMUD validation cohort from the Center for International Blood and Marrow Transplant Research (CIBMTR). The primary outcome was overall survival (OS). In multivariable analysis, haploidentical donors had a hazard ratio (HR) of 1.20 (95% confidence interval [CI], 0.93-1.54; P = .16) compared with the MMUD group. Donor age showed a nonlinear association with OS. These findings were corroborated by IPTW, matched-pair analyses, and CIBMTR validation analyses. Exploratory analysis revealed inferior OS for older (age of >50 years) haploidentical donor group compared with younger (age of <30 years) MMUD recipients (HR, 1.91; 95% CI, 1.21-3.01; P = .005). Our analyses suggest that although donor type may play a role, there was a more prominent role for donor age in influencing OS. Moreover, our findings indicate a potential nuance wherein the impact of donor type may vary by donor age. Further research, particularly with larger cohorts, is needed to fully elucidate the complex and potentially interacting roles of donor type and donor age, along with HLA factors.